The art of narrative and the rhetoric of persuasion in the “*Jīn Téng” (Metal Bound Casket) from the Tsinghua collection of manuscripts - Meyer, D (De Gruyter, 2014)
This article reconstructs the rhetoric of persuasion in the “Zhōu Wǔwáng yǒu jí” 周武王有疾 (King Wǔ of Zhōu suffered from illness), a text written on fourteen bamboo slips that is part of the Tsinghua collection of manuscripts and presumably dates to the Warring States period (ca. 481–222 BC). The “Zhōu Wǔwáng yǒu jí” has well-known transmitted counterparts in the Shàngshū and the Shǐjì, but in comparison with these texts, it largely omits explicit comment on the role of the Duke of Zhōu 周公 after the death of King Wǔ 武王. By taking this difference seriously and analysing the art of narrative in the text, this article reconstructs the social use of the text in the politico-philosophical discourse of the Warring States period. By drawing on theoretical work by Mieke Bal and Jan Assmann on narratology and memory production, this structural analysis of the “Zhōu Wǔwáng yǒu jí” further enables new insights into the circulation of knowledge, as well as into the production and circulation of texts at the time.